The Effect of Product Diversification on Corporate Social Performance in the Non-Renewable Energy Industry: Exploring the moderating effects of host country development and the Sustainable Development Goals - Renske Jongsma; Bart Jan Pennink (The Central European Review of Economics and Management (CEREM), 2020)
Aim: Building upon stakeholder and institutional theory, this paper investigates the relationship between product diversification and corporate social performance (CSP), thereby attempting to make essential contributions to the current literature. Based on an extensive literature review, it was expected that related, unrelated and total product diversification are positively related to CSP. Moreover, it was hypothesized that the exposure to weak institutional host country environments negatively affects the relationship between diversification and CSP, and that the Sustainable Development Goals (SDGs) have a positive effect on the relationship. Design / Research methods: The sample selected for this research is the non-renewable energy industry, since the industry shows great divergence in terms of corporate social responsibility (CSR) performance. In addition, the industry is highly susceptible to regulatory changes, while the Sustainable Development Goals have an enormous focus on the reliability and sustainability of energy, making it a highly relevant industry to study. This study analyzed 40 a 40 non-renewable energy firms over a time frame of seven years, by using OLS regression. Conclusions / findings: The results reveal that unrelated diversification is positively related to CSP, while the other forms of diversification show insignificant results. Contrary to expectations, the Sustainable Development Goals negatively affect the relationship between product diversification and CSP, while the moderating effect of exposure to weak institutional environments is insignificant. Originality / value of the article: Research on the relationship between product diversification on corporate financial performance is well-established, but the way in which product diversification influences a firm's behavior towards stakeholder demands and social concerns remains largely unexplored. Accordingly, the results of this study challenge existing theories while adding more context to the existing relationship, and in turn provide promising avenues for future research.
Keywords: 330; stakeholder theory; institutional theory; product diversification; corporate social performance; sustainable development goals; non-renewable energy industry